2016
DOI: 10.1002/ajmg.a.37664
|View full text |Cite
|
Sign up to set email alerts
|

COL1A1 and COL1A2 sequencing results in cohort of patients undergoing evaluation for potential child abuse

Abstract: Child abuse is a major public health concern that can explain a proportion of fractures in children. Osteogenesis imperfecta (OI) is the most common inherited syndrome that predisposes to skeletal fractures. We conducted a retrospective analysis of data from clinical, laboratory, and radiographic information from children evaluated for child abuse in which molecular testing for COL1A1 and COL1A2 genes was conducted. A total of 43 patients underwent molecular testing for OI. Pathogenic variants predicted to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Parents of children with OI often deal with the suspicion of CPA, by health teams during the initial treatment of fractures before the diagnosis is established 27 28 , 29 , 30 However, OI and CPA are not mutually exclusive 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents of children with OI often deal with the suspicion of CPA, by health teams during the initial treatment of fractures before the diagnosis is established 27 28 , 29 , 30 However, OI and CPA are not mutually exclusive 28 …”
Section: Discussionmentioning
confidence: 99%
“…Zarate et al suggested, in cases suspected of CPA and OI, to consider genetic testing only in the presence of clinical features of OI, or in cases with a family history of the disorder 29 . However, in cases of suspected nonaccidental injury, with unexplained fractures in children under investigation for OI, Pepin and Byers suggested evaluating the need for molecular analysis in some cases, considering that the clinical features of the disorder may not be observed during the clinical investigation 30 …”
Section: Discussionmentioning
confidence: 99%
“…28 Given reports of potential nonosseous findings and additional bone findings over time, it is important to evaluate the totality of the context of a case using information gathered from a multidisciplinary team when evaluating the etiology and significance of fractures for potential physical abuse. 8 One can neither exclude underlying bone disease merely on the basis of nonskeletal findings nor exclude abuse based solely on the presence of a VUS, even if the variant is determined to be clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…1 While few unsuspected cases are found, genetic testing for OI and other metabolic diseases of bone are common in the workup of potential child physical abuse involving fractures to assure consideration of all possible causes. [2][3][4][5][6][7][8] During the course of genetic testing, patients may have test results reported as "variants of unknown significance" (VUS) which are "sequence variants of uncertain pathogenicity in genes known to cause inherited Mendelian diseases in which molecular genetic testing has a proven clinical validity and utility." 9,10 VUS are identified with recognition that the clinical significance of any given sequence variant falls along a gradient, ranging from those in which the variant is pathogenic, likely pathogenic, likely benign, or benign.…”
Section: Introductionmentioning
confidence: 99%
“…Most pathogenic variants in COL1A1 are sporadic. 5 , 6 Because of the potential for mosaicism in an unaffected parent, variant-specific testing of the parents of AA was made available to help determine if the variant was inherited or arose de novo; in addition, this will provide information required for accurate genetic counseling for this family. Parents did not complete testing as of time of writing; if neither parent is found to carry the G224V variant in the COL1A1 gene, the possibility of mosaicism cannot be excluded, and offspring of either parent may be at risk of carrying this variant.…”
Section: Discussionmentioning
confidence: 99%